Faktor-Faktor Yang Mempengaruhi Keputusan Pembelian Mahasiswa UINSU Dalam Menentukan Produk Perawatan Wajah Skincare - Putri Rahmadany; Nurbaiti Nurbaiti; Juliana Nasution (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Current technological advances provide space for many people. Slowly, the development of a person's knowledge increases with the knowledge of advances in technology and information. And this concerns the many e-commerce and online media that are emerging, which people from teenagers to adults can enjoy. This is the main factor for marketers to aggressively carry out marketing with market trends that have been developing in recent times. Finally, there is competition between one industry and another in capturing the market. One industry that is currently attracting attention is the beauty industry, namely skincare.